Role of EGFL7 in human cancers: A review - de Oliveira, Cristiane [UNESP]; Gonçalves, Paola Gyuliane [UNESP]; Bidinotto, Lucas Tadeu [UNESP] (Wiley, 2023)
EGFL7 is a proangiogenic factor. It has been widely described with having a vital role in tubulogenesis and regulation of angiogenesis, mainly during embryogenesis and organogenesis. It has been mainly associated with NOTCH pathway, but there are reports showing association with MAPK and integrin pathways. Given its association with angiogenesis and these other pathways, there are several studies associating EGFL7 with carcinogenesis. In fact, most of the studies have pointed to EGFL7 as an oncogene, and some of them suggest EGFL7 expression as a possible biomarker of prognosis or use for a patient's follow-up. Here, we review the molecular pathways which EGFL7 is associated and highlight several studies describing the role of EGFL7 in tumorigenesis, separated by tumor type. Besides its role on angiogenesis, EGFL7 may act in other pathways as oncogene, which makes it a possible biomarker and a candidate to targeted therapy.
Keywords: angiogenesis; cancer; EGFL7; pathways